REVITALISASI NASKAH SYAIR: SEBUAH SOLUSI DALAM PENGEMBANGAN KREATIVITAS MAHASISWA UNTUK MENCINTAI BUDAYA LOKAL - Andriani, Tuti (Universitas Pendidikan Indonesia, 2015)
AbstractÂ Cultures were grown in campus tend to imitate the western culture, so that the local culture is ruled out. The local culture is considered ancient culture, so it does not show up in the form of creativity. Though Indonesia is rich with culture can be preserved in the campus. One of them is a manuscript poem, which is one form of the local culture of our nation. The text of the poem can be in the form of creative songs, drama, dance and others. One solution is to develop student creativity with the revitalization (revive) the text of the poem and developed through programs of student organizations in the field of arts and culture. So it is the first step to develop a sense of love of local culture.Keywords: manuscript poem, student activity, local cultureÂ AbstrakBudaya yang tumbuh di kampus cenderung meniru budaya barat, sehingga budaya lokal dikesampingkan. Budaya lokal dianggap budaya kuno, sehingga tidak muncul dalam bentuk kreativitas. Padahal Indonesia kaya dengan budaya dapat dipertahankan dalam kampus. Salah satunya adalah puisi naskah, yang merupakan salah satu bentuk budaya lokal bangsa kita.Teks puisi bias dalam bentuk yang kreatiflagu, drama, tari dan lain-lain. Salah satu solusinya adalah dengan mengembangkan kreativitas siswa dengan revitalisasi teks puisi dan dikembangkan melalui program organisasi mahasiswa di bidangsenidanbudaya. Jadi langkah pertama untuk mengembangkan rasa cinta budaya lokal.Kata-kata kunci: naskah syair, kreativitas mahasiswa, budaya lokal